How do the Learning Models of Teaching Game for Understanding and Problem-Based Learning Influence Fundamental Football Skills in Physical Education? Conducting an Analysis in the Elementary School Context - Nurhadi Santoso; Aris Fajar Pambudi; Heri Yogo Prayadi; Nur Sita Utami; Dewangga Yudhistira; La Ode Adhi Virama (OVS LLC, 2024)
Objectives. The study aimed to examine the influence of Teaching Game for Understanding (TGfU) and Problem-Based Learning (PBL) learning models on the elementary school students' fundamental football skills in physical education. Materials and methods. This study is classified as experimental research. The research design used was quasi-experimental.  A total of 46 elementary school students aged 10-11 years were the samples in this study. Of the 46 samples, 23 received the PBL learning model, whereas 23 received TGfU learning. Results. The research findings showed that: (1) there was a significant influence of the PBL learning model on fundamental football skills in physical education, with a p-value of 0.000 < 0.05; (2) the TGfU learning model demonstrated a substantial effect on fundamental football skills, with a p-value of 0.000 < 0.05; (3) a significant difference was observed between the PBL and TGfU learning models on fundamental football skills with a p-value of 0.000 < 0.05, and the difference between the two groups was 10.69. Conclusions. According to the results obtained, the PBL and TGfU learning models have a positive influence on fundamental football skills.